Die Struktur der Frage: »Wozu Rechtsgeschichte?« - Kenichi Moriya (Rechtsgeschichte - Legal History, 2003)
»Why legal history?« – a question asked repeatedly, so a new answer can no longer be expected. Therefore only the reason for asking must be explained. The question is not important, but rather the reference to it. It reminds us that all research in legal history should be useful for the discipline of modern law. There was never any doubt regarding the existence of a certain metaphysically united world of law. This fact has been illuminated by the great legal historian Sten Gagnér with the help of Wittgenstein’s philosophy of language analysis. He confronts the closed unity of law with a relative historical unity. So the idea of the unity of law has been made relative regarding history, but it was not yet questioned principally. The base of this is the connection of law and history started in Germany in modern times supposing there is a legal order in history. But it was Friedrich Carl von Savigny, founder of the Historical School, who – in view of the difficulty in surveying the legal situation of the time – showed basic doubts regarding the historical existence of the unity of law. Today jurists again find themselves in a semantic catastrophe. Many of them have therefore prematurely fled to what was already an offer, i.e. a pseudo-theory of systems or the history of doctrines. Yet a careful historical view could break this fetish. In the ruins, however, one needs new orientation. After criticising the fetish, orientation ought to be developed scientifically, i.e. purely artificially, based on material historically checked. Historical observation precedes the layout of legal history. »Legal history« as a concept is a faulty construction and should have been obsolete as a subject for some time.